Relationship between Smartphone Addiction with Social Anxiety in Adolescents - Primadiana, Dinda Berlian; Nihayati, Hanik Endang; Wahyuni, Erna Dwi (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2019)
Introduction: Excessive and uncontrolled use of smartphones in adolescents can cause addiction to users. One negative influence on uncontrolled smartphone use is the occurrence of social anxiety. The purpose of this study was to analyze the relationship between smartphone addiction and social anxiety in adolescents.Method: This research method uses descriptive analysis design with cross sectional approach. The population in this study were adolescents of smartphone users in SMA Antartika Sidoarjo. The number of samples of this study were 289 respondents using probability sampling techniques with a type of simple random sampling. The independent variable in this study is smartphone addiction, while the dependent variable is social anxiety. Data obtained by questionnaire instruments using Smartphone Addiction Scale (SAS) and Social Anxiety Scale for Adolescent (SAS-A), and analyzed using spearmans rho with significance <0.05. Result: The results of the statistical test show the value of p = 0,000 and the value of r = 0,255. The conclusion of this study, there was a relationship between smartphone addiction and social anxiety in adolescents of SMA Antartika Sidoarjo.Conclusion: Adolescents who experience smartphone addiction always fail to control the use of smartphone and assume that smartphone is important, while smartphone addiction can cause social anxiety in the form of fear of negative evaluation by others. Nurses need to do health education for adolescents related to smartphone addiction and the negative effects it causes.